HIV Testing Preferences Among MSM Members of an LGBT Community Organization in Los Angeles. (May 2017) - Medline, Alexandra; Daniels, Joseph; Marlin, Robert; Young, Sean; Wilson, Greg; Huang, Emily; Klausner, Jeffrey D.
Abstract : N/A: Lack of regular HIV testing puts African American, Asian, and Latino men who have sex with men (MSM) at high risk for HIV infection. Rapid self‐testing may be an effective option for these men. We explored acceptability, preferences, and usability of HIV self‐test kits with MSM of color using semi‐structured focus groups to discuss HIV testing history, reasons for testing, and self‐testing preferences. Participants ( n = 21) lived in Los Angeles, identified as MSM of color, and were 18‐35 years of age. Discussions were audio‐recorded, transcribed, and analyzed using grounded theory. Participants expressed needs for (a) accessibility, (b) privacy, (c) local support, and (d) access to testing professionals. Self‐testing for HIV infection may be an effective method for high‐risk MSM. Effective self‐testing programs need to consider accessibility, confidentiality, and support to increase routine testing. Community‐based organizations have an opportunity to increase HIV testing for MSM of color.